The process of healthy aging versus COVID-19 pandemic: nurses' performance in primary health care (Research, Society and Development, 2022)
This study aims to evaluate the impact of nurses' performance, during the COVID-19 pandemic, on the health of the elderly population in Primary Health Care. Through the qualitative research method, with exploratory characteristics, carried out through a semi-structured instrument with professional nurses working in basic units, analyzed using Minayo's Content Analysis Technique. The results found emerged from two thematic categories, “Health of the elderly population in times of the COVID-19 pandemic” and “Nursing consultation in times of a pandemic”. The research led us to conclude that the COVID-19 pandemic and the social isolation measure adopted caused a deficit in healthy aging, a decrease in the bond between the health unit and the elderly, in addition to an increase in the manifestations of anxiety and depression. The Nursing Consultation remained efficient, and proved to be of paramount importance for controlling the spread of the virus. But despite this, respondents noted a deficit in the healthy aging process.